2019
DOI: 10.1097/md.0000000000017812
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and antimicrobial resistance profiles of Pseudomonas putida infection in Central China, 2010–2017

Abstract: The aim of this study was to analyze the risk factors, clinical features, and antimicrobial resistance of Pseudomonas putida (P putida) isolated from Tongji Hospital in Wuhan, China. The data of 44 patients with P putida infections were retrospectively reviewed in this study. All cases of P putida strains were detected by the clinical laboratory of Tongji Hospital in the period of January 2010 to December 2017. Antimicrobial susceptibility testing was conducted using Kirby-Bauer method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…Despite this, many studies have reported that P. putida is the cause of severe illness in people with compromised immune systems, including a lethal case of bacteremia [ 48 ]. A recent study developed to analyze the risk factors, clinical characteristics, and antimicrobial resistance of P. putida isolated from Tongji Hospital in Wuhan (China) found high rates (75%) of drug resistance in P. putida isolates, particularly to trimethoprim/sulfamethoxazole (97.7%), aztreonam (88.6%), minocilin (74.3%), and ticarcillin/clavulanic acid (72.7%) [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, many studies have reported that P. putida is the cause of severe illness in people with compromised immune systems, including a lethal case of bacteremia [ 48 ]. A recent study developed to analyze the risk factors, clinical characteristics, and antimicrobial resistance of P. putida isolated from Tongji Hospital in Wuhan (China) found high rates (75%) of drug resistance in P. putida isolates, particularly to trimethoprim/sulfamethoxazole (97.7%), aztreonam (88.6%), minocilin (74.3%), and ticarcillin/clavulanic acid (72.7%) [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since P. putida is typically soil and/or aquatic bacterium, the focus of the research was on TCSs enabling tolerance to pollutants and plant colonization [ 11 , 12 , 14 , 15 , 19 ]. Albeit rarely, P. putida could also cause different types of infections in human beings [ 20 , 21 , 22 ]. Of special importance was often described multidrug-resistant phenotype of these isolates [ 20 , 21 , 22 ], while the pathogenic potential was isolate-specific [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates the demand for clear etiological discrimination in patients with fever. P. putida is widely found on hospital surfaces and moist environments and, as an opportunistic pathogen, can cause bloodstream infections [ 26 , 27 ]. Therefore, bloodstream infection surveillance is essential to characterize the public health threat [ 14 ].…”
Section: Discussionmentioning
confidence: 99%